ICE on Food: Talk related to foodways in the International Corpus of English - Kallen, Jeffrey (My University, 2015)
The frequency of occurrence of food verbs across ICE corpora is remarkably consistent, though ICE-CN is remarkably lower Food verbs favour light verbs, with decreasing frequency accounted for by semantic features: manner of action, type of subject, type of object, generality of outcome, desirability of outcome, etc. Observed frequencies do not necessarily correlate with grammatical expectations: some things are grammatically possible but rarely mentioned in ICE corpora. Food verbs interact with nominalisation: some potential verb forms occur more often as nominals, and nominalisations may fulfil various roles. Grammatical blocking applies despite the frequency of some light verbs. Food verbs interact with metaphor: FOOD may be a source by which TARGETS are understood, but FOOD may also be a target. Metaphors may point towards cognition, identity, experiences and conceptions of the body, health, pleasure, and pain.
Sociolinguistics Summer School 6 (SSS6)
Keywords: Digital Engagement; Digital Humanities; Identities in Transformation; Corpus Linguistics; English Language/Literature; Foodways; World Englishes; Communication; Culture